Augmented Reality Surgical Navigation in Spine Surgery to Minimize Staff Radiation Exposure. Issue 1 (1st January 2020) - Edström, Erik; Burström, Gustav; Omar, Artur; Nachabe, Rami; Söderman, Michael; Persson, Oscar; Gerdhem, Paul; Elmi-Terander, Adrian
Abstract : Study Design: Prospective observational study. Objective: To assess staff and patient radiation exposure during augmented reality surgical navigation in spine surgery. Summary of Background Data: Surgical navigation in combination with intraoperative three-dimensional imaging has been shown to significantly increase the clinical accuracy of pedicle screw placement. Although this technique may increase the total radiation exposure compared with fluoroscopy, the occupational exposure can be minimized, as navigation is radiation free and staff can be positioned behind protective shielding during three-dimensional imaging. The patient radiation exposure during treatment and verification of pedicle screw positions can also be reduced. Methods: Twenty patients undergoing spine surgery with pedicle screw placement were included in the study. The staff radiation exposure was measured using real-time active personnel dosimeters and was further compared with measurements using a reference dosimeter attached to the C-arm ( i.e., a worst-case staff exposure situation). The patient radiation exposures were recorded, and effective doses (ED) were determined. Results: The average staff exposure per procedure was 0.21 ± 0.06 μSv. The average staff-to-reference dose ratio per procedure was 0.05% and decreased to less than 0.01% after a few procedures had been performed. The average patient ED was 15.8 ± 1.8 mSv which mainly correlated with the number of vertebrae treated and the number of cone-beam computed tomography acquisitions performed. A low-dose protocol used for the final 10 procedures yielded a 32% ED reduction per spinal level treated. Conclusion: This study demonstrated significantly lower occupational doses compared with values reported in the literature. Real-time active personnel dosimeters contributed to a fast optimization and adoption of protective measures throughout the study. Even though our data include both cone-beam computed tomography for navigation planning and intraoperative screw placement verification, we find low patient radiation exposure levels compared with published data. Level of Evidence: 3 Abstract : Minimized staff exposure and reduced patient dose when augmented reality surgical navigation with 3D CBCT imaging is used for pedicle screw placement.